Regional Disparities in User Perception of Oral Health in Brazil’s Primary Care: An Integrative Review - Patrícia Silva Chaves; Yago Cesar Do Nascimento Souza; Yann Nobre Viana; Richelly Maria Rodrigues Holanda; Luciana Maria Arcanjo Frota; Mariana Ramalho de Farias; Jacques Antonio Cavalcante Maciel; Myrna Maria Arcanjo Frota Barros (Archives of Current Research International, 2025)
Aim: One of the alternatives used to evaluate the quality of dental services is the use of instruments, which provide an analysis of the user’s perception of health care in the service. The study aims to identify regional differences in the quality of oral health in Primary Health Care (PHC) from the perspective of service users. Study Design: This is an Integrative Literature Review. Methodology: This is a qualitative study using the Scielo, Bireme and PubMed databases. By crossing the descriptors “Health Assessment”, “Primary Health Care”, “Oral Health”, and “Brazil”, 661 studies were obtained, of which 14 were selected for meeting the inclusion criteria. No specific and relevant studies were found for other regions of Brazil, such as the North, Central West regions. Results: The results of the studies in the different regions of Brazil showed similarities. It was found that women, elderly people, those with low levels of education and socioeconomic status were more expressive in the use and evaluation of services, exposing the need for Public Policies that recognize the user’s vision as a means of improving the service provided by PHC.